Cuban ensiled feed and response of dairy cows - García López, R.; Lezcano, P.; González, María R. (Cuban Journal of Agricultural Science, 2021)
Twenty Siboney de Cuba cows, with similar lactation numbers, liveweight and milk production, were used to evaluate productive performance of dairy cows subjected to supplementation with Cuban ensiled feed, made from the fermentation of cassava or sweet potato. Cassava was used for the present experiment. The evaluation took place during dry season. Cows had 135 days of lactation, 7.6 kg of milk/day and a body condition of 3±0.1. They were divided into two groups, experimental and control, which were provided with following: a) 1 kg cow day1 of commercial concentrate during the milking time + 3 kg of Cuban silage and grazing, and b) 3 kg/cow/day-1 of commercial concentrate + evening-night grazing, respectively. Cows were milked twice (6 a.m. and 3 p.m.). After the second milking, they went to the corresponding paddocks together. The study lasted 140 consecutive days, which correspond to the evaluated period. The results indicated higher milk production, and significant (p ≤ 0.05) in the animals with the silage (8.7 vs. 8.1). However, the body condition (3.3 vs. 3.1) did not show significant differences, neither was protein in milk (2.9 vs. 2.9), which was low in both treatments. Results indicate that another nutritional alternative is available for dairy farming, which also represents a possibility to substitute feed imports and achieve better milk productions. Key words: milk production, dairy cows, silage